Exosomes Derived From Adipose-Derived Mesenchymal Stem Cells Ameliorate Radiation-Induced Brain Injury by Activating the SIRT1 Pathway - Liu, Mengdong; Yang, Yunshu; Zhao, Bin; Yang, Yuefan; Wang, Jing; Shen, Kuo; Yang, Xuekang; Hu, Dahai; Zheng, Guoxu; Han, Juntao (Frontiers in Cell and Developmental Biology, 2021)
Objective Studies have shown that the therapeutic effects of mesenchymal stem cells (MSCs) are mediated in a paracrine manner, mainly through extracellular vesicles such as exosomes. Here, we designed a study to investigate whether exosomes derived from adipose-derived mesenchymal stem cells (ADMSC-Exos) had protective effects in a rat model of radiation-induced brain injury and in microglia. Methods Male adult Sprague-Dawley (SD) rats were randomly divided into three groups: the control group, the radiation group (30 Gy), and the radiation + exosomes group (30 Gy + 100 ug exosomes). Meanwhile, microglia were divided into four groups: the control group, the radiation group (10 Gy), the radiation + exosomes group (10 Gy + 4 ug exosomes), and radiation + exosomes + EX527 group (10 Gy + 4 ug exosomes + 100 nM EX527). Tissue samples and the levels of oxidative stress and inflammatory factors in each group were compared. Results Statistical analysis showed that after irradiation, ADMSC-Exos intervention in vivo significantly reduced the levels of caspase-3, malondialdehyde (MDA), 8-hydroxydeoxyguanosine (8-OHdG), tumor necrosis factor-α (TNF-α), interleukin-4 (IL-4), and promoted the recovery of superoxide dismutase (SOD), catalase (CAT), IL-4, and IL-10. Moreover, ADMSC-Exos intervention inhibited microglial infiltration and promoted the expression of SIRT1. Furthermore, the results in vitro showed that the above effects of ADMSC-Exos could be reversed by SIRT-1 inhibitor EX527. Conclusion This study demonstrated that ADMSC-Exos exerted protective effects against radiation-induced brain injury by reducing oxidative stress, inflammation and microglial infiltration via activating the SIRT1 pathway. ADMSC-Exos may serve as a promising therapeutic tool for radiation-induced brain injury.